2003
DOI: 10.1007/s00203-003-0596-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Erythrobacter sp. strains from the upper ocean

Abstract: Seven strains of marine aerobic anoxygenic phototrophs belonging to the genus Erythrobacter were isolated. The strains were characterized regarding their physiological and biochemical properties, 16S rDNA and pufM gene sequences, morphological features, substrate preference, as well as pigment and lipid composition. All strains had functional type-2 reaction centers containing bacteriochlorophyll, served by small, light-harvesting complex 1, and were photosynthetically competent. In addition, large pools of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
157
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 31 publications
10
157
6
Order By: Relevance
“…Moreover, the BChl-a content per cell was significantly higher in the ultra-oligotrophic eastern basin than in the two other basins. Assuming that BChl-a quotas indicate the extent of phototrophic potential (Cottrell et al, 2006), our data suggest that reliance on phototrophy varied along the oligotrophic gradient and that nutrient and/or carbon limitation favors BChl-a synthesis in natural communities as it has been reported for AAP cultures (Koblížek et al, 2003;Yurkov and Csotonyi, 2009). …”
Section: Bacterial Productionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, the BChl-a content per cell was significantly higher in the ultra-oligotrophic eastern basin than in the two other basins. Assuming that BChl-a quotas indicate the extent of phototrophic potential (Cottrell et al, 2006), our data suggest that reliance on phototrophy varied along the oligotrophic gradient and that nutrient and/or carbon limitation favors BChl-a synthesis in natural communities as it has been reported for AAP cultures (Koblížek et al, 2003;Yurkov and Csotonyi, 2009). …”
Section: Bacterial Productionsupporting
confidence: 61%
“…In contrast, various reports showed that these organisms are abundant in eutrophic as well as in oligotrophic environments (Jiao et al, 2007;Koblížek et al, 2006;Yutin et al, 2007). Other authors suggested that nutrient concentrations (Mašín et al, 2008), attachment to particles Waidner and Kirchman, 2007) or light intensity (Koblížek et al, 2003;Shiba, 1991) may influence AAP bacterial abundance.…”
mentioning
confidence: 95%
“…These OTUs belong to a group of widespread oligotrophic budding organisms found in many aquatic environments but with no evidence for pathogenicity (Stahl et al, 1992;Weiner et al, 2000;Badger et al, 2005). Other taxa enriched in the Porites exudate amendments included OTUs closely related to the Alphaproteobacteria Sneathiella and Erythrobacter and to the Gammaproteobacteria Haliea and Thalassobius, all associated with free-living oligotrophic to mesotrophic coastal marine environments and with no known pathogenic lifestyles (Koblížek et al, 2003;Jordan et al, 2007;Urios et al, 2008;Park et al, 2012). Thus, the primary organisms selectively enriched by the coral exudates are widely distributed marine bacterioplankton, with no association with pathogenic or otherwise harmful lifestyles.…”
Section: Differential Growth Of Bacterioplankton Taxa On Dom Exudatesmentioning
confidence: 99%
“…In fully photosynthetic (autotrophic) organisms, this energy is used for inorganic carbon assimilation. However, carbon fixation activity in AAPs is negligible (Koblížek et al 2003). AAPs seem to possess a photoheterotrophic metabolism, as they require the supply of an organic carbon substrate and light serves only as an additional source of energy.…”
Section: Role Of Aerobic Anoxygenic Phototrophs In the Marine Carbon mentioning
confidence: 99%